Design and development of a self-propelled hydraulic floor crane - Safarzadeh, Daryoush (2012)
Crane is a device utilized for loading, unloading and transporting the loads. There are many types of cranes for various applications. Although cranes are profitable devices, they have a lot of problems. One of the most important problems of cranes is that they frequently generate hazards and accidents. Other problems relate to their performance and imperfection of systems. The purpose of this research is to design of a self-propelled hydraulic floor crane to prevent the hazards which are normally associated with the crane application in workshops and factories. The main focus was aimed at the remote controlling of the crane operations to reduce the hazards and improving the performance features such as rapidity, flexibility and maneuverability. The methodology employed in this thesis consists of design of crane's framework,design of systems, modeling of the crane by use of computer-aided design, and several investigations for development of the crane regarding payload sway, crane stability, field application and application of composite materials in the crane structure. Stability analysis of the crane was performed in static and dynamic situations. Equations of stability were derived and a crane was designed for field application. The results indicated that stability is based on the weight and center of gravity of crane and payload. Dynamics of payload sway was studied in a system with seven-degrees-of–freedom and equations of motion were derived by use of Lagrange's equation. Based on these equations, effect of hook and boom parameters on sway angles was studied and an anti-sway controller was designed. Results denoted that by increasing the mass and length of hook, sway of payload was diminished. Computer-aided finite element analysis was performed to compare three composite materials, carbon epoxy, graphite epoxy and glass epoxy with steel from the weight and strength point of view and glass epoxy was known as an appropriate ,substitute for steel in crane structure. The general research resulted in several findings and contributions such as: an advanced self-propelled hydraulic floor crane holding specifications in tables 5.8 and 5.9 for application in factories, workshops, fields and some of the hazardous environments, articulated hook, steer-by-switch system, sway brake system which is an autonomous system, and determination of the most appropriate composite material for crane frame-work. The hydraulic floor crane, articulated hook, steer-by-switch system and sway brake system are all new designs. For validating the research work, a scale-model prototype of the alternating current crane was built and tested. The entire crane operations could be controlled properly from afar via a control box located in the operator’s hands. The estimated fabrication cost of a full-scale crane is 16000 RM. Finally, it was concluded that use of the wire remote control system reduced the hazards by keeping operator far from the crane. Use of platform and sway brake system eliminated payload sway. Use of two electromotors, a three-piece boom, a compacted size, steering and drive systems, increased rapidity, flexibility and manueverability of the crane.